The key to success in biology learning : A meta-analysis of the effectiveness Problem-Based Learning (PBL) model on cognitive domain learning outcomes - Adityaningsih, Shafira Ramadhanty; Arum, Dewi Sekar; Ristanto, Rizhal Hendi; Isfaeni, Hanum; Gayatri, Dyah Ayu (Universitas Ahmad Dahlan, 2023)
Learning is a form of communication that is the basis for achieving information by students. The learning model that can improve students' activeness and learning outcomes is Problem Based Learning (PBL). The relevance found between the principles of the PBL model and the Biology learning process makes many studies linking the application of PBL with the achievement of cognitive learning outcomes. This study aims to determine the effectiveness of the Problem Based Learning (PBL) model on cognitive learning outcomes in biology using quantitative methods with meta-analysis techniques by reviewing 15 journal articles. The effectiveness of the PBL model on cognitive learning outcomes used the Effect Size (ES) formula. Based on the results obtained from the Effect Size test, the results obtained with moderate criteria ranged from 0.51 to 1.00 so it means that the Problem Based Learning (PBL) learning model has a positive impact on biology learning outcomes for students.